Mispricing and Investor Preference with Six Indicators of Blue-Chip Stocks’ Future Returns - Iman Lubis; Syamruddin Syamruddin; Irwansyah Irwansyah (International Journal of Business, Economics, and Social Development, 2020)
This research involves three variables: future returns, mispricing, and investor preference. The issue is that future returns in the markets are difficult to understand, especially for beginner, amateur investors. They are advised to focus on blue-chip stocks due to their safety in the market. The objective of this research is to find a connection from mispricing and investor preference to the future anomalies as indicators of mispricing and ten measurements as indicators of investor preference leading to three anomalies of mispricing and three measurements of investor preference. The three anomalies are asset growth, net operating assets, and total returns of blue-chip stocks. The methods used are descriptive statistics and associative statistics. In this research, we adopted eleven liabilities to total assets, while the three investor preferences are beta synchronous trading, book equity to market equity, and size. The descriptive statistics show that the asset growth, net operating asset, and size of eight companies are above the mean and the others are below it. Blue-chip stocks have excellent growth in assets, high operating assets, and high market capitalization. In addition, they have low liabilities (solvable), book value to market value (high return), and beta (low market sensitivity). The associative statistics used the multiple-regression cross-section Newey–West method and conducted the examination three times; that is, it tested mispricing with three indicators, investor preference with three indicators, and additional indicators between mispricing and investor preference. The result is not significant for the investor preference and mispricing index for the future returns of blue-chip stocks. The policy implication is that there is no divergence between fundamental and price security in the types of blue-chip stocks for future returns. Moreover, the institutional or individual investor does not impact future return’s stocks.